(untitled) (Brazilian Journal of Pharmaceutical Sciences, 2022)
In Nigeria, drug financing by the public has been challenged by financial constraints through public fund due to a limited fund available to the government to meet all its demands. The objectives of this study were to determine the variability of the hospital patient prices of same drugs under the PublicPrivate Partnership (PPP) and in Private Retail Community Pharmacy (PRCP), and to investigate the perceived efficiency and effectiveness of the PPP by comparing it with the Drug Revolving Fund (DRF) model in drug supply financing. This study was conducted in Nigeria utilizing a mixed method. Mann-Whitney U test analysis was used to compare the median drug price of the two facilities. The majority (76.19%) of the drugs were sold at a cheaper rate in the hospital than what was obtained in the PRCP with no significance difference (p > 0.05). Dominant responses from the focused group discussions supported the PPP model. This study shows that the median patient price of the basket of matched pairs of same drugs in the hospital under the PPP and in the PRCP was identical. Overall, the participants were of the opinion that the PPP model was more efficient and effective than DRFinthe financing drug supply.